KOMBINASI KOMPRES HANGAT DAN AROMATERAPI UNTUK MENGURANGI NYERI DAN GANGGUAN TIDUR LANSIA - Indah Purnamasari; Dinasti Pudang Binoriang (Jurnal Riset Daerah, 2024)
The elderly are people with a chronological age of 65 years or more. Along with the increase in chronological age there is an aging process that causes a decrease in physiological function in the form of tissue damage which can cause chronic pain to disturb sleep quality. To investigate the effectiveness of using a combination of warm compresses and aromatherapy to reduce chronic pain and sleep quality disorders in the elderly. This research uses descriptive case study method. The results of the assessment of the pain scale and sleep assessment before the intervention showed a pain scale of 4 and a PSQI score of 6. After the intervention was carried out 2 visits within 2 weeks, the results showed a pain scale of 3 and a PSQI score of 4